Galectin-9 Induced by Dietary Probiotic Mixture Regulates Immune Balance to Reduce Atopic Dermatitis Symptoms in Mice - Kim, Han Wool; Ju, Do Bin; Kye, Yoon-Chul; Ju, Young-Jun; Kim, Cheol Gyun; Lee, In Kyu; Park, Sung-Moo; Choi, In Soon; Cho, Kwang Keun; Lee, Seung Ho; Kim, Sung Chan; Jung, In Duk; et al. (Frontiers in Immunology, 2020)
Probiotics can be an effective treatment for atopic dermatitis (AD), while their mechanism of action is still unclear. Here, we induced AD in mice with 2,4-dinitrochlorobenzene and administrated YK4, a probiotic mixture consisting of Lactobacillus acidophilus CBT LA1, L. plantarum CBT LP3, Bifidobacterium breve CBT BR3, and B. lactis CBT BL3. Then, we have validated the underlying mechanism for the alleviation of AD by YK4 from the intestinal and systematic immunological perspectives. Administration of YK4 in AD mice alleviated the symptoms of AD by suppressing the expression of skin thymic stromal lymphopoietin and serum immunoglobulin E that excessive T-helper (Th)2 cell-mediated responses. YK4 inhibited Th2 cell population through induce the proportion of Th1 cells in spleen and Treg cells in Peyer’s patches and mesenteric lymph node (mLN). The proportions of CD103+ dendritic cells (DCs) in mLN and the spleen were significantly increased AD mice administered with YK4 when compared to AD mice. Furthermore, galectin-9 was significantly increased in the gut of AD mice administered with YK4. In vitro experiments were performed using bone marrow-derived DCs (BMDC) and CD4+ T cells to confirm the immune mechanisms of YK4 and galectin-9. The expression of CD44, a receptor of galectin-9, together with programmed death-ligand 1 was significantly upregulated in BMDCs following treatment with YK4. IL-10 and IL-12 were upregulated when BMDCs were treated with YK4. Cytokines together with co-receptors from DCs play a major role in the differentiation and activation of CD4+ T cells. Tregs proliferation and Th1 cell activation were enhanced when CD4+T cells were co-cultured with YK4-treated BMDCs. Galectin-9 appeared to contribute at least partially to the proliferation of Tregs. The results further suggested that DCs treated with YK4 induced the differentiation of naïve T cells toward Th1 and Tregs. At the same time, YK4 alleviated AD symptoms by inhibiting Th2 response. Thus the present study suggested a potential role of YK4 as an effective immunomodulatory agent in AD patients.